Application of solid waste of ductile cast iron industry for treatment of wastewater contaminated by reactive blue dye via appropriate nano-porous magnesium oxide. (January 2020) - Pourrahim, Solmaz; Salem, Amin; Salem, Shiva; Tavangar, Reza
Abstract: The solid waste of ductile iron industry, which contains at least 88.0% magnesium oxide, is one of the toxic materials, leading to land contamination. On the other hand, the removal of reactive dyes from wastewaters is difficult required effective adsorbent like nano-porous MgO. The novelty of present investigation is based on nano-porous magnesium oxide production by precipitation from the solid waste to treat the wastewaters contaminated by reactive dye which is abundantly used in the textile industry. In order to improve the adsorptive properties of extracted MgO powder, the combinations of surfactants, containing cetyltrimethylammonium bromide (CTAB), sodium dodecyl sulfate (SDS) and polyoxyethylene octyl phenyl ether (TX100) were applied based on the mixture design algorithm in the precipitation. The effects of processing factors such as surfactant composition, powder calcination temperature, surfactant dose and pH were evaluated on the removal efficiency. The results revolved that the combination of SDS and TX100, 1:1, plays an effective role in the production of particles with the appropriate average pore size, 16 nm. The adsorbent prepared in the optimum condition indicated a significant affinity for the removal of reactive dye which shows relatively pH-independent efficiency in the range of 3–9. The applied producer for fabrication of adsorbent eventually overcomes the pH-dependent problem for the toxic dye uptake, leading to produce the adsorbent with maximal adsorption capacity of 1000 mg g −1 . Graphical abstract: Image 1 Highlights: The dust due to manufacture of ductile cast irons creates a solid waste. A specific handling was considered to minimize the risk of land contamination. A safe process was presented to remove reactive dye via nano-porous MgO. An adsorbent with appropriate pore size, 16 nm, was produced by ecofriendly method. The novelty of work is to achieve a technique for pH-independent wastewater treatment. Abstract : The appropriated nano-porous magnesium oxide was extracted from solid waste of ductile iron industry and applied efficiently for recovery of wastewater contaminated by reactive dye.